2022
DOI: 10.1111/risa.13889
|View full text |Cite
|
Sign up to set email alerts
|

The role of trust and risk perception in current German nuclear waste management

Abstract: One of the lessons learned in various countries that have to deal with spent nuclear fuel is that finding a proper place and siting a repository for high-level nuclear waste (HLW) cannot be achieved without public consent. After decades of obstruction, Germany recently launched a new, participatory, site-selection process for the disposal of HLW in deep geological formations. Nonetheless, significant opposition is assumed. Therefore, citizens' trust in the procedure and the agents involved may be paramount. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…As laypeople develop more trust in experts or authorities in these technologies, they are more likely to perceive fewer risks (Siegrist 1999(Siegrist , 2000. With regard to nuclear technologies, social trust has been closely related to risk perception (Pijawka and Mushkatel 1991;Dunlap et al 1993;Ryu et al 2018;Seidl et al 2022). Biel and Dahlstrand (1995) found that trust in experts and authorities was strongly and negatively related to perceived risk; specifically, the correlation coefficient between trust and risk perception regarding a high-level nuclear waste repository amounted to −0.63.…”
Section: Knowledge Trust and Risk Perception Regarding Nuclear Eventsmentioning
confidence: 99%
“…As laypeople develop more trust in experts or authorities in these technologies, they are more likely to perceive fewer risks (Siegrist 1999(Siegrist , 2000. With regard to nuclear technologies, social trust has been closely related to risk perception (Pijawka and Mushkatel 1991;Dunlap et al 1993;Ryu et al 2018;Seidl et al 2022). Biel and Dahlstrand (1995) found that trust in experts and authorities was strongly and negatively related to perceived risk; specifically, the correlation coefficient between trust and risk perception regarding a high-level nuclear waste repository amounted to −0.63.…”
Section: Knowledge Trust and Risk Perception Regarding Nuclear Eventsmentioning
confidence: 99%